Education of the young child -present,past and future [videorecording] - Elkind,David (Washington, D.C. National Association for the Education of Young Children, 1987)
Program is a recording of David Elkind's keynote address at the 1986 NAEYC conference. His premise is that the image of children which society holds has varied throughout the centuries and that treatment of children differed based on those images. He cautions that early childhood educators must view children as they are, not as what popular imagery presents them.
Keywords: Education, Preschool